Influence of high hydrostatic pressure pretreatment on properties of vacuum-freeze dried strawberry slices. (30th November 2020) - Zhang, Lihui; Qiao, Yu; Wang, Chao; Liao, Li; Shi, Defang; An, Kejing; Hu, Jianzhong; Wang, Jun; Shi, Liu
Highlights: High hydrostatic pressure (HHP) improved the quality of vacuum-freeze dried strawberry slices. HHP pretreatment increased the anthocyanins content and redness of strawberry slices center. HHP pretreatment induced microstructure alteration and enhanced water mobility. HHP pretreatment damaged the cell structures and improved chromoplasts distribution. Abstract: Effects of high hydrostatic pressure (HHP) (50, 100, 150, 200 and 250 MPa) pretreatment on water mobility and distribution, drying duration, microstructure, color, cell wall fraction and tissue structure of strawberry slices were investigated. HHP significantly increased water mobility of the strawberry slices, resulting in the reduction of drying duration by 9–24%. As the pretreatment pressure was increased, redness value and anthocyanin content continuously increased, soluble pectin (SBP) content increased and then decreased, while the contents of protopectin (PTP) and cellulose decreased. After the HHP pretreatment, chromoplasts and moisture was distributed more uniformly in the strawberry slices. Microscopy images showed the formation of microscopic holes or channels in the matrix and the breakdown of tissue structure by HHP. Results suggested HHP pretreatment disrupted the integrity of the fresh strawberry which enhanced the drying efficiency and migration of the chromoplasts during the vacuum-freeze drying process.